Reading Proust : In Search of Wolf-Fish. - Paganini, Maria (Theory and history of literature., 1994)
What readers of Proust in English translation miss, along with most of his critics, is how precisely his writing works, how exactly his subtle craftsmanship weaves the spell that seems to enchant and distract those who encounter it. Even critics who take up the idiosyncrasies of Proust's text, Maria Paganini asserts, refuse to test its limits for fear of running into the writer's deliberate opacities. Reading Proust puts an end to this interpretive arrest by focusing on the specificity of Proustian writing, revealing the patterns of thought and play of words peculiar to Proust's language, and.